2018
DOI: 10.3126/jie.v13i1.20367
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake - Science in Himalayas: Ground Water Quality Change and its Implications

Abstract: In this paper, we discuss the pre-earthquake and post-earthquake groundwater scenario in context of Nepal. Nepal being one of the most earthquake vulnerable countries, the implications of earthquake in Nepal is considerable. Study requires not so only above the earth surface, but also in sub-surface conditions. Of various geo-physical and geo-chemical, subsurface conditions, this particular study concerns with groundwater chemical parameters. Before the occurrence of earthquake, groundwater chemistry has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…However, in case of Kathmandu valley previous studies and this study demonstrated the microbial contamination of water is quite common before and after the earthquake (Pant, 2010;Pant et al 2016;Uprety et al, 2017). In a country like ours where the use of ground water is prevalent for domestic and drinking purpose microbial contamination of water may have severe effect on human health (Banjara, Paudel, 2017). Physical and chemical alteration of ground water may occur after earthquake however this study exhibits that physical and chemical parameters generally are within the NDWQS (1996) guidelines while the microbial contamination of water could pose risk to the public health.…”
Section: Microbiological Analysismentioning
confidence: 55%
See 2 more Smart Citations
“…However, in case of Kathmandu valley previous studies and this study demonstrated the microbial contamination of water is quite common before and after the earthquake (Pant, 2010;Pant et al 2016;Uprety et al, 2017). In a country like ours where the use of ground water is prevalent for domestic and drinking purpose microbial contamination of water may have severe effect on human health (Banjara, Paudel, 2017). Physical and chemical alteration of ground water may occur after earthquake however this study exhibits that physical and chemical parameters generally are within the NDWQS (1996) guidelines while the microbial contamination of water could pose risk to the public health.…”
Section: Microbiological Analysismentioning
confidence: 55%
“…Changes in post-earthquake water quality parameters have widely been studied and changes in chemical and microbial parameters have been reported (Banjara, Paudel, 2017;Uprety et al, 2017). However, in case of Kathmandu valley previous studies and this study demonstrated the microbial contamination of water is quite common before and after the earthquake (Pant, 2010;Pant et al 2016;Uprety et al, 2017).…”
Section: Microbiological Analysismentioning
confidence: 67%
See 1 more Smart Citation
“…The water quality of the wells located in the Western area of the city also corresponds to the zone where the aquitard presents the largest drawdown percentages (>60%), as reported in areas with clay thickness smaller than 25 m (Auvinet et al, 2017), a condition that may also influence water quality. Local, intermediate and regional flux type wells were used in order to assess if there was a difference in water quality according to flow regime.…”
Section: Discussionmentioning
confidence: 75%
“…Seismic zones are related to the origin of the lacustrine plain in which Mexico City was built. According to Auvinet et al (2017) the lacustrine plain was formed by progressive silting of the basin reservoir, due to the rising of Sierra del Chichinautzin. Silting with volcanic products and river drift propitiated conditions for the formation of a lake system within the Basin of Mexico.…”
Section: Geological and Geophysical Settingmentioning
confidence: 99%